CRYOGENICS - Ahuja, L.D. (SCHOOL SCIENCE, 2012)
Just as the quest for Atomic Energy enabled us to achieve very high temperatures (of the order of hundreds of thousands of degrees) and gave us what is now called the Plasma State, our exploration of the outer space has brought us in contact with temperatures reaching almost absolute zero (-273 C). The coldest spots on the face of this earth have a temperature around -68°C (in the Arctic Circle). The term 'Cryogenics' applies to the study of materials at temperatures ranging from -100°C to almost absolute zero (-273°C). This is the range where gases turn into liquids; steel, even rubber, becomes as brittle as glass; metals become super-conducters and even living cells pass into a state of suspended animation.